Studi Penggunaan Batu Gunung Bittuang Kabaputen Tana Toraja Sebagai Bahan Campuran AC-WC Dengan Variasi Perendaman Berulang - Sulle, Alfrianto Barangan; Nurdin, Abdul Rahim; Mallawangeng, Tamrin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Mountain stone is a rock that contains lime and is often found in highland areas. The need for road infrastructure development in each region, especially in Tana Toraja Regency, is increasingly being developed, therefore the need for materials for development, especially road infrastructure, is increasing. The aim of this research is to determine the properties and characteristics and also analyze the properties and effects of hot asphalt mixture (AC-WC) of Mount Bittuang stone. This research uses Mount Bittuang stone. Briquette making refers to the 2018 General Specifications for Bina Marga. Sample testing is carried out using the Marshall method. The test results show that Mount Bittuang stone can be used as a material in hot asphalt mixtures because the characteristics and testing properties of the asphalt mixture are within the 2018 Bina Marga specification limits and the effect of using Mount Bittuang stone as a substitute for coarse and fine aggregates, on the properties and performance in AC-mixtures. but still within the specifications used with the stability value, namely without immersion 1311.05 depending on the length of immersion with the value, 0 day 1053.13 on the 6th day 1045.53 on the 12th day 1022.59 and on the 18th day 1023.93.